Improving pasture productivity through legume introduction - TRIPATHI, K P; RATHORE, S S; GARG, V K (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1999 and 2000 on 4 different pasture systems, viz natural pasture, pasture of buffel grass (Cenchrus ciliaris L.), intercropping of C. ciliaris and legume., i e lablab bean [Dolichos lablab L.; syn Lablab purpureus (L.) Sweet] and legume alone. Introduction of legume as an mtercrop m the grass resulted significant mcrease m dry-matter and protein yield over other treatments Application of 20 kg N/ha significantly mcreased the. dry-matter productivity (15.33-26.98%). The land-utilization efficiency (139%) and net returns/ha (Rs 2 623) of the pasture land were enhanced owing to introduction of legume in the pasture system. The organic carbon content was the highest (0.34%) under the C. ciliaris plots. Incorporation oflegume wIth the grass slightly reduced the organiC carbon (0.33 %) In the Soil. The build up of organic carbon was less under natural pasture than C. ciliaris. Similar to the organic carbon, grass pasture also reflected the highest structural stability over the other treatments. Intercropping of legume with grass Increased mineralizable N (46.71 % in surface and 33.86% in subsurface) in the soil and also enhanced the activities of dehydrogenase and phosphatase soil enzymes, indicating better microbial activities in the soil.